Academic Degree as a Predictor of Student Interest in Green University-Based Learning - Hesti Umiyati; Ronald Tehupuring (Jurnal Pendidikan Progresif, 2026)
This study aims to examine the influence of academic degrees on students' interest in green university-based learning processes. This means that this study can provide empirical evidence regarding the role of academic qualifications in supporting sustainability-oriented education at the university level. This study employed a mixed-methods approach with a sequential explanatory design. The quantitative phase was conducted through a survey of 132 students administered via a Likert-scale questionnaire, and the data were analyzed using simple linear regression to test the research hypotheses. The qualitative phase was conducted through in-depth interviews with selected participants, which were analyzed thematically to strengthen, validate, and enrich the quantitative results, thereby strengthening decision-making. The results show that academic degree has a positive and significant effect on student interest (β = 0.766; p < 0.05), with a coefficient of determination (R²) of 0.598, indicating that 59.8% of the variation in student interest is explained by lecturer expertise. Furthermore, qualitative findings indicate that lecturers with higher academic degrees are perceived as more credible, systematic, and able to relate learning materials to sustainability issues, thereby increasing student engagement, motivation, and active participation in the learning process at the university. Lecturers' expertise, as reflected in their academic qualifications, plays a crucial role in increasing students' interest in sustainability-oriented learning. Therefore, improving lecturers' academic qualifications and strengthening their pedagogical competencies are strategic steps in supporting the implementation of green university-based learning in higher education. This situation indicates that the success of green university implementation is determined not solely by university policies and infrastructure but also by the quality of human resources. Keywords: academic degree, student interest, green university, sustainability in higher education.